The Adoptation of the Training Plan of Bachalor Specialty “Informatics” of the Kherson State University to the Computing Curricula (CС) (Journal of Information Technologies in Education (ITE), 2008)
The main information about the traditions of Informatics learning in Ukraine is described, the recommendations of CC are examined, the adopted training plan of Informatics specialty and the choice of subjects is described in the present article.